2003
DOI: 10.1046/j.1365-2265.2003.01822.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hypothyroxinaemia during early pregnancy and subsequent child development: a 3‐year follow‐up study

Abstract: Maternal hypothyroxinaemia during early gestation is an independent determinant of a delay in infant neurodevelopment. However, when fT4 concentrations increase during pregnancy in women who are hypothyroxinaemic during early gestation, infant development appears not to be adversely affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
432
4
23

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 660 publications
(479 citation statements)
references
References 31 publications
20
432
4
23
Order By: Relevance
“…The effect of reduced thyroid function on fetal development appears to be the most severe during the first trimester of pregnancy (Kooistra et al, 2006;Morreal de Escobar et al, 2007). Even relatively modest reductions in thyroid hormone levels in early pregnancy may be associated with adverse effects on fetal nervous system (Pop et al, 1999(Pop et al, , 2003Kooistra et al, 2006). For these reasons, this analysis focuses on estimating the contribution of drinking water to total perchlorate exposures received by reproductive-age women in the United States (18-45 years old), likely the most sensitive demographic group for which exposure data are available.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of reduced thyroid function on fetal development appears to be the most severe during the first trimester of pregnancy (Kooistra et al, 2006;Morreal de Escobar et al, 2007). Even relatively modest reductions in thyroid hormone levels in early pregnancy may be associated with adverse effects on fetal nervous system (Pop et al, 1999(Pop et al, , 2003Kooistra et al, 2006). For these reasons, this analysis focuses on estimating the contribution of drinking water to total perchlorate exposures received by reproductive-age women in the United States (18-45 years old), likely the most sensitive demographic group for which exposure data are available.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] In humans, consequences of maternal thyroid hormone deficiency depend on the level of the deficiency and their specific developmental timing (reviewed in Zoeller and Rovet 25 ). Similarly, in the rat, maternal thyroid hormones play a role in fetal thyroid economy, and prenatal thyroid hormone insufficiency affects adult behavior leading to learning deficits and hyperactivity.…”
mentioning
confidence: 99%
“…Accordingly, maternal thyroid function is of great importance for the foetus during the first half of pregnancy. Haddow et al [2] and Pop et al [3] reported that maternal hypothyroidism and hypothyroxinaemia occurring in the first half of pregnancy might be harmful to embryo-foetal brain development and lead to intellectual retardation in the offspring. Consequently, a debate over the recommendation to perform routine screening for thyroid hormone deficiency in pregnant women has ensued [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%